2020
DOI: 10.1109/access.2020.2993693
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Allocation of Capacitor and Distributed Static Compensator in Radial Distribution Networks Using Multi-Objective Improved Golden Ratio Optimization Based on Fuzzy Decision Making

Abstract: In this paper, multi-objective reactive power compensation based on optimal and simultaneous allocation of capacitors and distribution static compensator (DSTATCOM) in radial distribution networks based on fuzzy decision making is proposed with the aim of reducing power losses cost, reactive investment cost and reducing voltage deviations considering power loss reduction factor (PLRF) to identify candidate buses. Optimal location and size of reactive resources is determined based using multi-objective improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Proposed by A. Noori et al is a hybrid allocation of capacitors and distributed static compensators in power distribution systems through multi-objective improved golden ratio optimization method (MOIGROM) and a fuzzy decision making process [3]. In this case, the MOIGROM has two objectives, including voltage violations and total installation cost corresponding to the equipment and related active power losses.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Proposed by A. Noori et al is a hybrid allocation of capacitors and distributed static compensators in power distribution systems through multi-objective improved golden ratio optimization method (MOIGROM) and a fuzzy decision making process [3]. In this case, the MOIGROM has two objectives, including voltage violations and total installation cost corresponding to the equipment and related active power losses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was found that typical objectives for capacitor planning generally include the minimization of active power losses and investment [3], [4], [6]. Constraints were also sometimes applied concurrently with the optimization or afterward upon the resulting Pareto set to ensure power system operational compliance for proposed capacitor configurations by limiting voltage violations and THD [5]- [7], [15].…”
Section: Figurementioning
confidence: 99%
“…By contrast, traditional mechanical throwing and cutting equipment are cheaper. An optimal configuration combined with those types of equipment can reduce the investment cost of the dedicated equipment [20], [21]. In [20], a golden ratio optimization algorithm was adopted to determine the optimal and simultaneous allocation of capacitors and distribution static compensators.…”
Section: B Summary Of Challenges Of Previous Studiesmentioning
confidence: 99%
“…In the future, these alternative energy-generating industries will soon dominate the entire community (Neaime et al, 2018;Ozili, 2018;Noori et al, 2020;Oxford Economics, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%